The removal mechanism and performance of tetrabromobisphenol A with a novel multi-group activated carbon from recycling long-root Eichhornia crassipes plants. Issue 43 (9th August 2019) - Liu, Lili; Chen, Xin; Wang, Zhiping; Wang, Xixi; Lin, Sen
Abstract : MGAC showed excellent adsorption performance for TBBPA and provide an ecologically friendly way to deal with eutrophic plants. Abstract : Long-root Eichhornia crassipes has shown great potential in eutrophication treatments while the heavy disposal of its plants limits its large-scale application. In this study, the adsorption of TBBPA by a novel multi-group activated carbon (MGAC), prepared from the reaped long-root Eichhornia crassipes plants has been investigated as a potential recycling and remediation technology. The MGAC showed great adsorption performance for aqueous TBBPA in that the adsorption could arrive at equilibrium in 4 h and the saturated adsorption capacities could reach up to 110.7, 110.5 and 75.50 mg g −1 at 20, 30 and 40 °C, respectively. Based on the analysis of adsorption processes, it was confirmed that π–π interaction and hydrogen bonding were the major impetuses for the adsorption and the oxygen-containing functional groups on the MGAC surface could facilitate the adsorption by either electron sharing or electron transfer. In addition, the thermodynamic results showed that the adsorption was a spontaneous and exothermic reaction. Futhermore, the MGAC could be regenerated easily by 5% NaOH solution and retained over 50% of its initial capacities for TBBPA after 5 reprocessing cycles. These results indicate the promising application of MGAC in the wastewater treatment for TBBPA removal and a resource recycling method for the long-root Eichhornia crassipes plants.